Anacardic Acid Isolation from Cashew Seed Skin - Aliefman Hakim; Jamaluddin Jamaluddin; I Nyoman Loka; Saprizal Hadisaputra; Ayu Rizki Mujiyanti (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2021)
Research on the isolation of anacardic acid compounds from cashew nut shells has been carried out. This study aims to develop a method of isolating anacardic acid compounds from cashew nut shells in an easier way but still produces pure compounds. In this study, isolation and identification of anacardic acid compounds contained in CNSL were carried out. The results of anacardic acid isolation contained in CNSL form a thick brown extract with a characteristic dark odor. Anacardic acid was isolated using a maceration method using methanol as a solvent. The results of the isolation of anacardic acid compounds were then tested for purity using a thin layer chromatography test (TLC) using an eluent or a mobile phase of methanol: chloroform. Furthermore, anacardic acid compounds were identified using IR spectroscopy and UV-vis spectroscopy. This identification was carried out to prove that the compound obtained was indeed an anacardic acid compound. The identification results found that the compound isolated in this study was indeed an anacardic acid compound. It can be compared with the structure of existing anacardic acid compounds.